The integrated biological indicator as a tool for detection of river pollution - Sohaili, Johan; Kasan, Nor Azman; Ibrahim, Zaharah; Hashim, Normala (2005)
Water quality of the River Pontian Kecil is influenced by both organic and inorganic nature of pollutant. The predominant sources of Pontian Kecil contamination at Johor, Malaysia are agricultural activities and pollution derived from urban area located in the area within the river corridor. This river and its tributaries is important to human as water supply, domestic water uses, irrigation, fisheries and recreation. It should be controlled under the Water Quality Management Plan (WQMP) as beneficial water. The use of biological indicator is to predict local condition that can result in a variety of spatial scales that biological indicator can be addresses. Biological indicator was applied as a tool to measure the water resources condition, biological restoration goals, enforcement and compliance, and establishing baseline data for Nature Resource Damage Assessment (NRDA). The effect of future development along the river corridor on water quality could not be ruled out. A study on water quality, biological indicator and the existing species of flora and fauna are used in observing the effects of the activities within the river. The relevant sources are identified, an appropriate prevention and control measures